"Don't praise the day before the sunset": Paremiology in the study of depressiveness. (September 2021) - Wołońciej, Mariusz; Wilczewski, Michał; Kreitler, Shulamith
Psychology and psychiatry are in a constant search for an adequate model of affective disorders. Psychology has classified depression as a mood disorder, but a growing literature links mental disorders with socioculturally relevant ways in which people experience and express distress. With this study, we link depression with proverbs as omnipresent narrative structures and mini-theories that help people interpret reality and categorize personal experience. Proverbs are omnipresent narrative structures that describe, explain, and prescribe human behavior. Hence, we offer a paremiological approach to better understand the minds of the depressed. Our tenet is that proverbs may also reflect people's mental states and attitudes by conveying different levels of optimism versus pessimism. We evidence empirically that proverbs convey optimistic and pessimistic attitudes and, thus, have the capacity to capture peoples' mental states. Moreover, we show that this capacity is limited for people with high depressiveness. Finally, we discuss how proverbial thinking links collective experience and wisdom imprinted in proverbs with an individual's mental states, which has important research and practical implications.